A "Crucial Catch": Examining Responses to NFL Teams' Corporate Social Responsibility Messaging on Facebook. (August 2018) - Devlin, Michael; Sheehan, Kim
This study investigated the National Football League's (NFL) communication efforts of its annual Corporate Social Responsibility (CSR) campaign, "A Crucial Catch, " and the subsequent social media engagement from the public. A content analysis was conducted examining how NFL teams communicate their CSR efforts on Facebook using Charity Support Behaviors (CSB) and framing as our guide and then measuring which of these types of social media posts were most effective for increasing positive social media engagement. The extent that each team's season record affected CSR messaging was also examined, underscoring the importance of winning and losing and its effect on social media engagement. The results of this study yield a comprehensive analysis of the types and frequency of messages used to communicate CSR activity on Facebook. Results provide best-practice recommendations for sports organizations using social media to communicate activities to external stakeholders (i.e., fans) that will benefit the cause and increase positive social media engagement (e.g., likes, shares, and comments).